An injectable hyperthermic nanofiber mesh with switchable drug release to stimulate chemotherapy potency - Chen, Lili; Fujisawa, Nanami; Takanohashi, Masato; Ebara, Mitsuhiro (Frontiers in Bioengineering and Biotechnology, 2022)
We developed a smart nanofiber mesh (SNM) with anticancer abilities as well as injectability and fast recovery from irregular to non-compressible shapes. The mesh can be injected at the tumor site to modulate and control anticancer effects by loading the chemotherapeutic drug, paclitaxel (PTX), as well as magnetic nanoparticles (MNPs). The storage modulus of the mesh decreases when applied with a certain shear strain, and the mesh can pass through a 14-gauge needle. Moreover, the fibrous morphology is maintained even after injection. In heat-generation measurements, the mesh achieved an effective temperature of mild hyperthermia (41–43 ℃) within 5 min of exposure to alternating magnetic field (AMF) irradiation. An electrospinning method was employed to fabricate the mesh using a copolymer of N-isopropylacrylamide (NIPAAm) and N-hydroxyethyl acrylamide (HMAAm), whose phase transition temperature was adjusted to a mildly hyperthermic temperature range. Polyvinyl alcohol (PVA) was also incorporated to add shear-thinning property to control the interactions between polymer chains derived from hydrogen bonding. The “on-off” switchable release of PTX from the mesh was detected by the drug release test. Approximately 73% of loaded PTX was released from the mesh after eight cycles, whereas only a tiny amount of PTX was released during the cooling phase. Furthermore, hyperthermia combined with chemotherapy after exposure to an AMF showed significantly reduced cancer cell survival compared to the control group. Subsequent investigations have proven that a new injectable local hyperthermia chemotherapy platform could be developed for cancer treatment using this SNM.